Pengaruh Kompensasi, Lingkungan Kerja Fisik Dan Fasilitas Kerja Terhadap Produktivitas Kerja Karyawan CV. Mukti Mulyo - Nadia Puspita Sari; Taufik Akbar; Erwin Syahputra (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to explain and prove the hypothesis regarding the influence of compensation, physical work environment and work facilities on the work productivity employees of CV. Mukti Mulyo. Where this research uses a descriptive research model with a quantitative approach method with a non-probability sampling technique, namely a saturated sample method, with a population of 32 employees and a sample of 32 respondents or all employees used as samples. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, partial test (t test), simultaneous test (F test) and determination test (R2) which are processed using the SPSS version 25 data processing program. The research results obtained are that compensation has a partial and significant effect on employee work productivity with a significant t test value of 0.016 < 0.05. The physical work environment has a partial and significant effect on employee work productivity with a significant t test value of 0.001 < 0.05. Work facilities have a partial and significant effect on employee work productivity with a significant t test value of 0.022 <0.05. Compensation, physical work environment and work facilities have a simultaneous and significant effect on employee work productivity with a significant F test value of 0.000 <0.05.